1996
DOI: 10.1248/bpb.19.1238
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginseng Radix on GLUT2 Protein Content in Mouse Liver in Normal and Eqinephrine-Induced Hyperglycemic Mice.

Abstract: The oral administration of the water extract of Ginseng Radix (GR) to normal and epinephrine-induced hyperglycemic mice caused a significant decrease in the blood glucose level 4 h after its administration. The hepatic content of facilitative glucose transporter isoform 2, liver type glucose transporter (GLUT2) protein content from mouse liver significantly increased in the orally GR-treated normal and epinephrine-induced hyperglycemic mice compared to that in the controls. These results suggest that the hypog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
35
0
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 0 publications
2
35
0
1
Order By: Relevance
“…Still, an intriguing property of ginseng is its hypoglycemic effect, which is supported by several animal studies (11)(12)(13). Additionally, 2 studies in humans have confirmed ginseng' s glucose-lowering ability (14,15).…”
mentioning
confidence: 91%
See 1 more Smart Citation
“…Still, an intriguing property of ginseng is its hypoglycemic effect, which is supported by several animal studies (11)(12)(13). Additionally, 2 studies in humans have confirmed ginseng' s glucose-lowering ability (14,15).…”
mentioning
confidence: 91%
“…An effect on insulin sensitivity has been shown twice in mice and cell lines. Chinese ginseng preparations were observed to increase GLUT2 protein in the livers of normal and hyperglycemic mice (12) and glucose uptake into sheep erythrocytes in a dosedependent manner (33). DPG-3-2, a water extract of ginseng, was also shown to stimulate insulin secretion directly, increasing biosynthesis in different preparations of mice islets and rat pancreases (34).…”
mentioning
confidence: 99%
“…Ginseng extract has been shown to lower blood glucose level in both diabetic and glucose-loaded healthy animals (Ohnishi et al, 1996). The proposed mechanisms for the hypoglycemic effect of ginseng including enhanced hepatic glucose uptake (Ohnishi et al, 1996), enhanced insulin secretion and sensitivity (Zhang et al, 2008;Gao et al, 2013), enhanced glucagon-like peptide-1 secretion , enhanced lipid metabolism (Xie et al, 2005), facilitated immune homeostasis (Hong et al, 2012), reduced food intake and body weight (Attele et al, 2002;Xiong et al, 2010), or a combination of these modes (Zhang et al, 2008;Hong et al, 2012;Gao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…12,[29][30][31] Ginseng, often described as the "king herb," has been used as an anti-diabetic herb for several thousand years in Asia. The anti-diabetic actions of ginseng might mediate through a variety of mechanisms including actions on improving systemic insulin sensitivity, 32) increasing the activity of a glucose transporter protein, 33) and reducing glycogenolysis, thus restraining hyperglycemia. 34) Moreover, ginseng treatment increased insulin release from pancreatic ÎČ-cells, which is probably caused by increasing ÎČ-cell stimulation and insulin synthesis.…”
mentioning
confidence: 99%